Development of an Integrated Human-Computer Interactive Model for Improved User Experience in Gesture-Controlled Smart Mirrors - Ayorinde Joseph Olanipekun; Olubusola Olufunke Nuga; Peter Olamide Onabanjo; Emmanuel Uchechukwu Ogbodo; Samuel Blessing Owusu (ABUAD Journal of Engineering Research and Development)
The advancement of smart technologies has led to the development of innovative home automation devices, with smart mirrors emerging as a modern convenience tool. This paper focuses on the design and implementation of a gesture-controlled smart mirror, incorporating a two-way mirror, monitor, raspberry pi, gesture-enabled camera, power adaptor and a swipeable interface to enhance user interaction. The objectives of the paper include designing a comprehensive smart mirror using CAD, integrating gesture control technology through Python's OpenCV package, constructing a functional prototype utilizing the Magic Mirror software, and conducting extensive testing. Key tests conducted include usability test to assess user interaction, functionality test to validate gesture control and mirror operations, data analysis for performance metrics, and visibility test for optimal display quality. Functionality test showed an average gesture detection accuracy of 92.5%, with the swipe left and swipe right gestures achieving the highest accuracy. In the usability test, the average response time across all gestures was 0.75 seconds, which is within the acceptable range for real-time interaction. Other performance indicators like error rate, average user satisfaction, device uptime and gesture latency were tested. These results demonstrated the effectiveness of the gesture-controlled interface, with the prototype showing high accuracy in gesture recognition and overall positive user feedback in terms of usability and reliability. The findings of this work suggest that the developed smart mirror could serve as a valuable addition to smart home environments, offering a seamless and interactive experience for users.